3D transesophageal echocardiography in TAVR. Issue 10 (30th June 2020) - Bleakley, Caroline; Monaghan, Mark
Abstract: Recently, there has been an increasingly minimalistic approach to transcatheter aortic valve replacement (TAVR), with most procedures now performed under conscious sedation without real time transesophageal echocardiography (TEE) guidance. Proponents of echo should not feel discouraged by this; it is the initial insights that were gained with procedural TEE during the early years of TAVR that have allowed the procedure's gradual maturation and sophistication. Experienced centers that have promoted extensive TAVR TEE programs continue to maximize the benefits of echocardiography in both procedural planning and execution. Critical to this is the understanding of 3D TEE, allowing the annulus to be sized accurately, relevant neighboring anatomy defined, and complications flagged. This review will outline the current application of 3D TEE in TAVR and discuss challenges and opportunities for 3D echocardiography in this field.